An Urban Food Situation: the popular sales off food in the center of Campinas - Antipon, Livia Cangiano (Geografares, 2018)
The article approaches the study of the Urban Food Situation as an analytical way to understand contemporary cities; The center of Campinas has a diverse economic circuit, dynamized by the flow of workers that pervades the region daily. Resulting from an unequal city, a popular food trade stands out from this economic circuit. For this analysis, one makes use of the theory of the two circuits of the urban economy and of the socially necessary market. Thus, the center of the city of Campinas is discussed as the shelter of the poor urban food practices.
Keywords: Urban Food Situation; Center of Campinas, São Paulo; Brazil; popular sales off food